Some data concerning the dynamics of alginic acid and mannitol in the brown alga Cystoseira barbata - Mîrza, Maria (Cercetări Marine - Recherches Marines, 2026)
The determinations of alginic acid and mannitol in the brown alga Cystoseira barbata, from the Romanian Blak Sea coast, from January 1971 to December 1971, indicate a significant seasonal variation of those compounds: there are two annual maxima of alginic acid, representing 17% and 21% of dry substance, in April and October, respectively, and two annual minima representing 8.5% and 21% of dry substance, in January and July; there are two annual minima of mannitol, representing 24% and 21% of dry substance, in April and October, and two annual minima, representing 7.7% and 12% in January and August.